Body and Mind, and Vice-Versa, or the Continuing Performative Sexual Revolution in Portuguese Arts - Madeira, Claudia (2022)
In Everyday Life in the Modern World, first published in 1968, Henri Lefebvre presents the sexual revolution as the first instance of the cultural revolution. This aspect has remained one of the central themes of contemporary activism, often reflecting the relationship between social and artistic performance, between art and life or even presenting life as art. Hinged on this relationship, we will discuss some Portuguese art works produced between the 1960s and the present: from dictatorship into democracy. These works build a continuing thematic thread related to what has been termed the “intensification of bodies” but also, as we intend to explore in this article, to a necessary “intensification of minds”, concerning eroticism, sexuality and love.